Children's views on taking medicines and participating in clinical trials. Issue 9 (14th June 2019) - Nordenmalm, Sofia; Kimland, Elin; Ligas, Franca; Lehmann, Birka; Claverol, Joana; Nafria, Begonya; Tötterman, Ann Marie; Pelle, Benjamin
Abstract : Introduction: Limited information is available on the views of children taking medicines and participating in clinical trials. These views may contribute to a better understanding of what can be improved on in the development of medicines from their perspective. Objective: To collect children's views on taking medicines and participating in clinical trials. Materials and methods: A question-based survey was conducted among children living in European Union countries between January and August 2015. Results: Almost 900 children aged 10–17 years from Finland, Germany, Sweden, Spain and Hungary responded. Almost 40% had a chronic health condition. The most commonly used pharmaceutical forms were solid or liquid medicines for oral use and injectable medicines. Bad taste and pain during administration were reported as common problems. Of 785 respondents, 17% had been taking part in a clinical trial. Most respondents would potentially agree to take part in a clinical trial because the investigational medicine might improve their own health or that of other children. Concern that the investigational medicine might be harmful was the main reason to refuse participation, if asked to. Over half of the respondents were willing to learn more about clinical trials, preferably online. Conclusions: It is necessary to involve children in the development of age-appropriate pharmaceutical forms and in the design of clinical trials. Children and their carers should be provided with age-appropriate medical information in the most suitable channels. We have identified some common problems that children experience when taking medicines, and we conclude that children are interested in learning more and giving their opinions on clinical trials.